Exploring the Chemopreventive Potential of Soybean Phytochemicals Targeting BRCA1 Protein: A Molecular Docking Study - Liviandari, Regina; Estuningtyas, Ari; Kusmardi; Erlina, Linda (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2026)
Breast cancer remains a significant cause of cancer-related mortality among women globally, highlighting the importance for preventive strategies targeting early molecular events. BRCA1 plays a critical role in maintaining genomic stability through DNA repair mechanisms. However, the potential of soybean phytochemicals to modulate BRCA1 activity at the molecular level, particularly through computational approaches, has not been extensively explored. This study aimed to evaluate the chemopreventive potential of soybean phytochemicals targeting the BRCA1 protein using an in silico approach. A total of 32 compounds were prepared and docked into the BRCA1 binding site using Autodock Tools 1.5.7, followed by interaction analysis and visualization, prediction of pharmacokinetic and toxicity profiles using SwissADME, pkCSM, and ProTox. The results showed that the top compounds exhibited binding energy ranging from -6.04 to -8.07 kcal/mol, which were lower than the reference compound. Interaction analysis revealed stable binding with key amino acid residues, including Met1775, Leu1839, and Lys1702 through hydrogen and hydrophobic interactions. Among the evaluated compounds, daidzin showed the most balanced profile in terms of binding affinity, interaction relevance, and favorable ADMET properties. This study provides a systematic in silico evaluation of soybean phytochemicals targeting BRCA1 and highlights their potential as candidates for breast cancer chemoprevention.